One‐pot synthesis chlorin e6 nano‐precipitation for colorectal cancer treatment Ce6 NPs for colorectal cancer treatment - Zhongxing Miao; Yujie Wang; Shengjie Li; Min Zhang; Meng Xu (IET Nanobiotechnology, 2021)
Abstract The drug nanoparticles free of additional carriers hold great promise in drug delivery and are suitable for the therapy of cancers. Herein, we developed a one‐pot method to prepare chlorin e6 (Ce6) nano‐precipitations (Ce6 NPs) for effective photodynamic therapy of colorectal cancer. The drug loading of Ce6 NPs was around 81% and showed acceptable stability, high biocompatibility as well as effective reactive oxygen species (ROS) generation capability. As a result, the Ce6 NPs can produce significantly elevated ROS upon laser irradiations and achieved better anticancer benefits than free Ce6.